Delving into the 'emotional storms': A thematic analysis of psychoanalysts' initial consultation reports1. (June 2015) - Pérez, Alejandra; Crick, Penelope; Lawrence, Susan
<x xml:space="preserve">Abstract</x> Psychoanalysts' written reports on initial consultations are a window into the complexities of a crucial aspect of psychoanalytic work. However, systematic research in this area has largely focused on patients' demographic factors or standardized measures. The present study looked at reports of all the consultations taking place at the London Clinic of Psychoanalysis over one calendar year (N = 100). The aim was to explore psychoanalysts' different explicit styles of working and reporting as well as further understanding implicit processes used in thinking and writing about each particular consultation experience. A thematic analysis revealed a set of themes that related to a style of working and thinking about the consultation process as a dyadic experience, where the interaction, affective reactions and contact made between the two are the focus when thinking of making a recommendation for psychoanalysis. The majority of the reports had an open, exploratory quality. The writing of reports appears to give the analyst an opportunity to process the consultation experience and arrive at a more triangular position. Writing reports is a more valuable part of the consultation process than has formally been recognized and acknowledged. The limitations of this study as well as the relevance of these findings for future research are discussed.